Case gender and severity in cerebral palsy varies with intrauterine growth. Issue 5 (25th April 2005) - Jarvis, S; Glinianaia, S V; Arnaud, C; Fauconnier, J; Johnson, A; McManus, V; Topp, M; Uvebrant, P; Cans, C; Krägeloh-Mann, I
Abstract : Background: There is an unexplained excess of cerebral palsy among male babies. There is also variation in the proportion of more severe cases by birth weight. It has recently been shown that the rate of cerebral palsy increases as intrauterine size deviates up or down from an optimum about one standard deviation heavier than population mean weight-for-gestation. Aims: To determine whether the gender ratio or the severity of cases also varies with intrauterine size. Methods: A total of 3454 cases of cerebral palsy among single births between 1976 and 1990 with sufficient data to assign case severity (based on intellectual impairment and walking ability) and to compare weight-for-gestation at birth to sex specific fetal growth standards, were aggregated from nine separate registers in five European countries. Results: The greater the degree to which growth deviates either up or down from optimal weight-for-gestation at birth, the higher is the rate of cerebral palsy, the larger is the proportion of male cases, and the more severe is the functional disability. Compared to those with optimum growth the risk of more severe cerebral palsy in male babies is 16 times higher for those with a birth weight below the 3rd centile and four times higher when birth weight is above the 97th centile. In contrast, for mild cerebral palsy in female babies the excess risks at these growth extremes are about half these magnitudes. Conclusions: Among singleton children with cerebral palsy, abnormal intrauterine size, either small or large, is associated with more severe disability and male sex.